The role of proactive therapeutic drug monitoring in guiding infliximab therapeutic optimization in pediatric patients with Crohn's disease: A retrospective study - Junya Song; Huihui Zhang; Huihua Zhang; Ximing Xu; Xiaohua Liang; Yongfang Liu; Xiaomei Song; Hong Guo; Xue Zhan; Jinlin Song; Xiaoqin Zhou (Pediatric Discovery)
Abstract Therapeutic drug monitoring (TDM) plays an important role in guiding treatment plan adjustments and clinical outcomes in Crohn's disease. To evaluate the role of TDM‐guided optimization of infliximab dosage in patients with pediatric Crohn's disease. Medical records of patients with pediatric Crohn's disease who were treated with infliximab and had proactive TDM from June 2020 to June 2022 at the Children's Hospital of Chongqing Medical University were included. Baseline influencing factors for infliximab trough concentration (TC) and clinical outcomes before and after the treatment change were analyzed to assess the value of adjusting treatment in the patients. Forty‐six patients (male‐to‐female ratio = 1.55:1, age <18 years) were included. Univariate and multivariate analyses showed that hormone exposure (odds ratio: 0.042, 95% confidence interval: 0.002–0.924, p = 0.044), perianal lesions (5.813, 0.984–34.349, p = 0.052), simplified endoscopic score for Crohn's disease (1.656, 1.065–2.577, p = 0.025), and total protein (TP) (0.851, 0.749–0.967, p = 0.014) were correlated with infliximab TC. Shortening the treatment interval increased the infliximab TC (pre vs. post = 1.69 ± 0.8 vs. 12.03 ± 6.64, p = 0.001, n = 12) after 93.9 ± 37.47 days, decreased the pediatric Crohn's disease activity index and simplified endoscopic score for Crohn's disease, and increased the biochemical remission, clinical remission, endoscopic remission, and endoscopic response rates; however, there was no statistical significance. Hormone exposure, perianal lesions, simplified endoscopic score for Crohn's disease, and TP levels before the first infliximab use affected the infliximab TC. Shortening the treatment interval can improve infliximab TC levels and clinical outcomes.